Decision Support System for Outstanding Students’ Selection Using TOPSIS - Suryani, Irma; Sani, Asrul; Budiyantara, Agus; Pusparini, Nur Nawaningtyas (Jurnal Riset Informatika, 2024)
In the school environment, determining outstanding students holds significant importance. High academic achievement among students and a low failure rate reflect the overall quality of education. Based on the interviews, it is known that the assessment process for outstanding students at school still needs to be revised, and the current decision-making system needs to consider other factors, resulting in suboptimal selection processes. To address this issue, implementing a Decision Support System (DSS) is necessary to assist the school in selecting the best students. DSS is an interactive system providing access to data and modelling information, designed to support decision-making in both structured and unstructured situations. This DSS will be designed using the Technique for Order of Preferences by Similarity to an Ideal Solution (TOPSIS) as the alternative ranking method. The final results indicate that using the TOPSIS method in this decision support system can improve efficiency and accuracy in selecting outstanding students in the school environment.